A model-based optimization of microalgal cultivation strategies for lipid production under photoautotrophic condition. (2nd February 2019) - Ryu, Kyung Hwan; Kim, Boeun; Lee, Jay H.
Highlights: Optimized various strategies of microalgae cultivation using a mathematical model. Batch, continuous, fed-batch, semi-batch, and two-stage operations are evaluated. Semi-batch and C&B two-stage operations show best performances. CAPEX requirements are analyzed for a given annual production volume. Issues in startup, initial cell concentration and chemical consumption are analyzed. Abstract: Increasing the lipid production rate stands as one of the challenges for achieving economic feasibility of microalgal biorefinery. Various bioreactor operation strategies have been considered for culturing microalgae, including batch, continuous, fed-batch, semi-batch, and two-stage operations. However, since the previous studies used different experimental criteria, it is hard to draw a conclusion about their relative performances. Motivated by this, the present study compares lipid productivity performances and capital expenditures of the various operation strategies after their operating conditions are optimized. The optimal condition for each strategy is determined by performing a model-based optimization to maximize lipid productivity, which is a good indicator of the overall economics. The two-stage operation with continuous-batch serial connection (w/ stress condition) and the semi-batch operation (w/o stress condition) show outstanding performance compared to the other types of operation. Also, start-up, initial cell concentration, and chemical consumption, which are critical factors in large-scale cultivation, are analyzed.